Erwin A. Schmidl: Habsburgs jüdische Soldaten 1788–1918 - Weber, Elisabeth (Medaon, 2015)
Erwin A. Schmidl: Habsburgs jüdische Soldaten 1788-1918, Wien/Köln/Weimar: Böhlau Verlag 2014, 264 S., ISBN: 978-3-205-79567-4, EUR 29,90. Besprochen von Elisabeth Webe